International Pediatric ORL Group (IPOG) laryngomalacia consensus recommendations. (July 2016) - Carter, John; Rahbar, Reza; Brigger, Matthew; Chan, Kenny; Cheng, Alan; Daniel, Sam J.; De Alarcon, Alessandro; Garabedian, Noel; Hart, Catherine; Hartnick, Christopher; Jacobs, Ian; Liming, Bryan; et al.
Abstract: Objective: To provide recommendations for the comprehensive management of young infants who present with signs or symptoms concerning for laryngomalacia. Methods: Expert opinion by the members of the International Pediatric Otolaryngology Group (IPOG). Results: Consensus recommendations include initial care and triage recommendations for health care providers who commonly evaluate young infants with noisy breathing. The consensus statement also provides comprehensive care recommendations for otolaryngologists who manage young infants with laryngomalacia including: evaluation and treatment considerations for commonly debated issues in laryngomalacia, initial work-up of infants presenting with inspiratory stridor, treatment recommendations based on disease severity, management of the infant with feeding difficulties, post-surgical treatment management recommendations, and suggestions for acid suppression therapy. Conclusion: Laryngomalacia care consensus recommendations are aimed at improving patient-centered care in infants with laryngomalacia.